Programa de liderazgo transformacional para mejorar las relaciones interpersonales de los estudiantes de la I.E. N° 821254 de la Compuerta en el año 2016 - Nureña Ruiz, Anita Emperatriz (2019)
ABSTRACT The purpose of the research was to determine the level of influence of the application of a Transformational Leadership Program in the Interpersonal Relationships of the students of the I.E. N ° 821254 of La Compuerta in 2016. As a study methodology, the Pre Experimental design was used, applying the "Pre Test and Post Test with only one group". The study population consists of all the students of the primary level and the sample is of 34 students of the primary level of the I.E. N ° 821254 of the hamlet of La Compuerta. The independent variable was the Transformational Leadership Program and the dependent variable was interpersonal relationships. Having as conclusion that the level of the Interpersonal Relations in the Pre-test, of the students of the I.E. No. 821254 of La Compuerta in 2016, it is described that of the 34 intervened, 11 (32.4) indicate that there is a high level of lack of interpersonal relationships and with a score of 23 (67.6). The qualifiers of interpersonal relationships in the pre-test shows that the students of the primary level at a level of Achievement 85% (A) In Process 12% (B) In Start 3% (C) and in Achievement Outstanding 0 % (AD) which we can say that the optimal rating scale in Primary Education in terms of achievements. There is a significant correlation between the program of transformational leadership and the interpersonal relationships of students at the primary level of the I.E. No. 821254 of La Compuerta where we can conclude by saying that the students in the Pre Test obtained an average score of 65.74 points, increasing in the Post Test to 96.80 points.